Validation of the movement disorder society criteria for the diagnosis of 4‐repeat tauopathies. Issue 1 (30th September 2019) - Respondek, Gesine; Grimm, Max‐Joseph; Piot, Ines; Arzberger, Thomas; Compta, Yaroslau; Englund, Elisabet; Ferguson, Leslie W.; Gelpi, Ellen; Roeber, Sigrun; Giese, Armin; Grossman, Murray; Irwin, David J.; et al.
Abstract: Background: The Movement Disorder Society criteria for progressive supranuclear palsy introduced the category "probable 4‐repeat (4R)‐tauopathy" for joint clinical diagnosis of progressive supranuclear palsy and corticobasal degeneration. Objectives: To validate the accuracy of these clinical criteria for "probable 4R‐tauopathy" to predict underlying 4R‐tauopathy pathology. Methods: Diagnostic accuracy for 4R‐tauopathies according to the established criteria was estimated retrospectively in autopsy‐confirmed patients with progressive supranuclear palsy and corticobasal degeneration (grouped as 4R‐tauopathies), and Parkinson's disease, multiple system atrophy, and frontotemporal lobar degeneration (grouped as non‐4R‐tauopathies). Results: We identified 250 cases with progressive supranuclear palsy (N = 195) and corticobasal degeneration (N = 55) and with and non‐4R‐tauopathies (N = 161). Sensitivity and specificity of "probable 4R‐tauopathy" was 10% and 99% in the first year and 59% and 88% at final record. Conclusions: The new diagnostic category "probable 4R‐tauopathy" showed high specificity and may be suitable for the recruitment of patients with progressive supranuclear palsy and corticobasal degeneration into therapeutic trials targeting 4R‐tauopathy. The low sensitivity underpins the need for diagnostic biomarkers. © 2019 International Parkinson and Movement Disorder Society